Novel barrier-reinforcing method based on mobile nodes re-deployment in WSN - Guoyong DAI; Weiyuan SHI; Kezhen YING; Qingzhang CHEN; Keji MAO (Dianxin kexue)
Barrier coverage in wireless sensor networks plays a key role in intrusion detection system.How to build a robust barrier is a key problem in this research area.In order to fix the weak points caused by nodes’ energy consumption,a reinforcing method was proposed to strengthen the barrier by re-deploying some mobile nodes,in which set-based max-flow algorithm was employed to calculate the number of weak points.The vulnerability degree of each weak point was analyzed so that the mobile nodes can move to these spots to reinforce the whole barrier.Experiment results show that the algorithm can effectively strengthen the barrier,extend the survival time of the barrier and the algorithm complexity is relatively lower.